Effect Of Job Embeddedness, Job Satisfaction, And Organizational Commitment On Employee Turnover Intention - Damas Aunul Kholiq; Miftahuddin Miftahuddin (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This study was conducted to determine the effect of job embeddedness, job satisfaction, and organizational commitment towards employees turnover intention. The authors assume that job embeddedness, job satisfaction and organizational commitment significantly affect employees turnover intention. This study uses a quantitative method approach with multiple regression analysis. Population in this study are 402 employees of Bank BCA Kanwil Alam Sutera and 211 employees as a sample. Taken with non probability sampling technique. In this study, using a scale of turnove intention based on Mobley, Horner, & Hollingsworth (1978), job embeddedness scale based on Mitchell, Holtom, Lee, et al. (2001 job satisfaction scale based on Spector (1997) , and organizational commitment scale based on Allen & Meyer (1990). The result shows there was significant mutual effect of the job embeddedness, job satisfaction, and organizational commitment to employees turnover intention. Results of minor hypothesis test known that only two independent variable has asignificant influence with employees turnover intention, which is sacrifice organization and reward. DOI: 10.15408/tazkiya.v22i1.8154